Providing a Lean and Agile Supply Chain Model in Project-Based Organizations - Mohammadreza Zahedi; Morteza Abbasi; Shayan Naghdi Khanachah (goodwood publishing, 2020)
Purpose: One key difference between project-oriented and routine organizations is their supply chain, which requires distinct management approaches. This article presents a conceptual model of lean and agile supply chains in project-oriented organizations by examining lean functions and supply chain agility. Research Methodology: This study is descriptive-analytical in method and applied in purpose. The statistical population included managers and supply chain experts from project-based organizations, with a sample of 105 people selected via purposive sampling. A researcher-made questionnaire was used to gather data, and structural equation modeling with the PLS software was applied to test the model. Results: The findings indicate that 114 identified items significantly explain their related components. The model fit study results, based on convergent validity, Cronbach's alpha, and other validity indices, show that the model is in the desired condition. Conclusions: This study presents a conceptual model for lean and agile supply chains in project-oriented organizations, emphasizing the need for flexibility and external knowledge engagement. The model’s components are valid, and further research could explore its practical application across various sectors. Limitations: This research only described Knowledge Based Centre. Contribution: Organizations realized that relying solely on existing knowledge is insufficient to compete in a competitive environment and began seeking knowledge beyond their organizational boundaries. Customers were recognized as valuable knowledge resources, necessitating interaction with leading organizations.